Government and NGO Interventions in Dryland Agriculture :a study of two projects in Andhra Pradesh - Put, M.(ed.) Dijk, Meine Pieter van.(ed.) (New Delhi Manohar, 2000)
Analyses of field work done in the four villages in the Rangareddi and Mahabubnagar districts of Andhra Pradesh, India, by Dept. of Geography, University of Madras and Indo-Dutch Programme on Alternatives in Development.
Keywords: Arid regions agriculture; Agricultural innovations -- India--Andhra Pradesh